How effective are ACF‐funded couple relationship education programs? A meta‐analytic study. Issue 3 (17th January 2022) - Hawkins, Alan J.; Hokanson, Sarah; Loveridge, Eden; Milius, Emily; Duncan, Misha; Booth, McCall; Pollard, Brittany
Abstract: Since 2006, the U.S. Administration for Children and Families (ACF) has allocated $1.2 billion to a Healthy Marriage and Relationship Education (HMRE) policy initiative that provides grants to community organizations to support relationship education (RE) services for lower income couples and individuals. The policy aim was to help disadvantaged couples and individuals form and sustain healthy, stable relationships and marriages. A significant body of research on the effectiveness of these programs has now accumulated. This meta‐analytic study reviews all evaluation research reports of adult couple relationship education (CRE) programs supported by the ACF policy initiative to examine their impact on an array of couple, family, and individual well‐being outcomes. Overall, our review of 32 control‐group studies found a range of small but significant effects for couple relationship quality ( d  = .114), relationship skills ( d  = .132), mental health ( d  = .074), and coparenting ( d  = .033), but non‐significant effects for relationship stability, parenting, and child well‐being. Supplemental analyses with 19 1‐group/pre‐post studies showed larger effects. Planned moderator analyses explored significant heterogeneity in most effects, however, revealing interesting implications for practice and research going forward. Resumen: Desde 2006, la Administración para los Niños y las Familias (Administration for Children and Families, ACF) de los Estados Unidos ha destinado $1.2 mil millones a una iniciativa de una política de Capacitación en Relaciones y Matrimonios Saludables (Healthy Marriage and Relationship Education, HMRE) que ofrece subvenciones a organizaciones comunitarias con el objetivo de financiar servicios de capacitación en relaciones para parejas y personas de bajos recursos. El objetivo de la política es ayudar a las parejas y a las personas desfavorecidas a formar y mantener relaciones y matrimonios estables y saludables. Actualmente se ha acumulado un número considerable de investigaciones sobre la eficacia de estos programas. En este estudio metaanalítico se analizan todos los informes de evaluaciones de investigaciones sobre programas de capacitación en relaciones de parejas adultas financiados por la iniciativa de políticas de la ACF con el fin de estudiar su efecto en diversos resultados de bienestar en las parejas, las familias y las personas particulares. En general, en nuestro análisis de 32 estudios de grupos de referencia se hallaron distintos efectos pequeños pero significativos para la calidad de la relación de pareja ( d = .114), las habilidades relacionales ( d = .132), la salud mental ( d = .074), y la cocrianza ( d = .033), y efectos no significativos para la estabilidad relacional, la crianza y el bienestar de los niños. Los análisis complementarios con 19 estudios previos y posteriores de un grupo demostraron efectos más importantes. Sin embargo, los análisis planificados de moderadores analizaron la heterogeneidad significativa en la mayoría de los efectos y revelaron consecuencias interesantes para la práctica y la investigación en el futuro. 摘要: 自2006年以来，美国儿童和家庭管理局(ACF)已向健康婚姻和关系教育(HMRE)政策倡议拨款达12亿美元，向社区组织提供赠款，支持为低收入伴侣和个人提供关系教育(RE)服务。该政策的目的是帮助处境不利的伴侣和个人建立和维持健康、稳定的关系和婚姻。关于这些项目的有效性，现在已经积累了大量的研究。这项元分析研究回顾了所有由ACF政策倡议支持的成人伴侣关系教育（CRE）项目的评估研究报告，以检查它们对一系列伴侣、家庭和个人福祉的影响。总的来说，我们对32个对照组研究的审查发现，对伴侣关系质量（d=0.114）、关系技能（d=0.132）、心理健康（d=0.074）和共同育儿（d=0.033）有一系列小而重要的影响，但对关系稳定性、养育子女和儿童幸福感没有明显的影响。对19个单组/前哨研究的补充分析显示了更大的影响。然而，计划调节因子分析探讨了大多数效果的重大异质性，揭示了对实践和研究的有趣影响。